The NBN Futures Forum: Learning from International Experience - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2020)
On 25 February 2020, TelSoc hosted the third NBN Futures Forum in Melbourne on the theme of learning from international experience for Australia’s National Broadband Network. Three speakers discussed various aspects of the topic, including comparisons via league tables, the experience in New Zealand, and the need for good broadband to participate in the global economy. Discussion following the speeches brought out a need to understand the range of demands for broadband from a variety of end users and industrial applications.